2009
DOI: 10.1016/j.red.2008.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Model uncertainty and liquidity

Abstract: Extreme market outcomes are often followed by a lack of liquidity and a lack of trade. This market collapse seems particularly acute for markets where traders rely heavily on a specific empirical model such as in derivative markets like the market for mortgage backed securities or credit derivatives. Moreover, the observed behavior of traders and institutions that places a large emphasis on "worst-case scenarios" through the use of "stress testing" and "value-at-risk" seems different than Savage expected utili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
83
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(93 citation statements)
references
References 27 publications
4
83
0
1
Order By: Relevance
“…Routledge and Zin (2009) investigated the impact of ambiguity on liquidity and found that investors behave under multiple-prior preferences. Ozsoylev and Werner (2011) also studied the effect of ambiguity on liquidity and they proved that ambiguity can be associated with illiquid financial markets, since market makers chose not to participate in the market when there is lack of information.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Routledge and Zin (2009) investigated the impact of ambiguity on liquidity and found that investors behave under multiple-prior preferences. Ozsoylev and Werner (2011) also studied the effect of ambiguity on liquidity and they proved that ambiguity can be associated with illiquid financial markets, since market makers chose not to participate in the market when there is lack of information.…”
Section: Introductionmentioning
confidence: 99%
“…This idea is inspired from the theoretical literature (e.g., Routledge & Zin, 2009;Ozsoylev & Werner, 2011), which showed the effect of ambiguity on liquidity.…”
Section: Introductionmentioning
confidence: 99%
“…Cont [6] reports that financial market participants usually distinguish between two types of risk, commonly referred to as 'market risk' and 'model risk' according to Routledge and Zin [23]. While market risk is quantified by the specification of a probabilistic model for the uncertain quantities, model risk is usually dealt with by a worst-case approach involving, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In such situations agents' decision are made by reference to the worst scenario, its decision weight being dependent on degree of 'probability imprecision'. The perception of it is increasing in situations of doubts about the relevance of previously used decision models (Routledge and Zin [2001]). In this case the stabilization does not induce a rapid return to the normal level.…”
Section: Choice Of Substitution Currency: Theories and Estimation Hypmentioning
confidence: 99%
“…Existing studies demonstrate the high level of dollarization of Latin American economies ) but also of economies of transition (Sahay and Vegh [1995]). Existing studies focus on the dollarization in a large sense which includes the use of all foreign currencies inside country.…”
mentioning
confidence: 99%